Synthesis and characterization of carbon nano-structures for methane storage - Danna, A. B. M.; Iyuke, S. E.; Fakhru'l-Razi, Ahmadun; Chuah, T. G.; Atieh, Muataz A.; Al-Khatib, Ma'an Fahmi Rashid (ISEIS - International Society for Environmental Information Sciences, 2003)
Natural gas (NG), which contains about 95% methane is currently gaining global acceptance as fuel for combustion engines because it is environmentally friendly and clean, naturally abundant, and cheaper than gasoline or diesel. Upon combustion when compared to gasoline or diesel it emits much less carbon dioxide (a major greenhouse gas) as well as several other air pollutants. However, the biggest challenge facing NG use as fuel for the transport industries is its storage. Therefore, we have synthesised carbon nano-structures using a typical floating catalyst chemical vapour deposition (FCCVD) in a horizontal tubular reactor, which was fabricated in the Department of Chemical & Environmental Engineering, University Putra Malaysia. Ferrocene was used as the catalyst (Fe) precursor, benzene as the carbon source, whiles a mixture of hydrogen and argon was used as the carrier gas for both ferrocene and benzene vapours. The temperatures for the synthesis were varied between 900 to 11500C to produce three distinct nanostructures, which are carbon nanotubes, nanofibers and carbon nanoporous balls. Upon scanning with scanning electron microscope (SEM) and transmission electron microscope (TEM), the diameters of the carbon nano-particles obtained ranged from 89 to 340 nm. Further characterisation with the Accelerated Surface Area and Porosimetry system (ASAP 2000), using liquid N2 (77 K) for the Brunaur-Emmett-Teller (BET) surface characterisation, the surface areas, pore sizes and micropore volumes were found to range from 3.4653 to 52.7961m2/g, 0.63975 to 8.03282 nm, and 4.18x 10-4 to 130.42 x 10-4 cm3/g, respectively for several weight of samples. The low values of surface areas and micropore volumes could be attributed to the inability of the N2 molecules to access the nanoporosity of the particles, little quantity and the lightweight of the particles (0.019, 0.099, 0.227, 0.185 0.1883g). A remarkable storage capacity of methane was achieved with the carbon nanoporous balls, compared to the other nanoparticles, which showed no adsorption at atmospheric temperature and pressure.